Formation of the microstructure and properties of strontium hexaferrite magnets using powder injection molding - B. D. Chernyshev; I. V. Schetinin (Тонкие химические технологии)
Objectives. The study set out to investigate the possibility of production strontium hexaferrite permanent magnets using powder injection molding (PIM) technology, which involves casting granules highly filled with ceramic powder. After obtaining the initial granulate based on organic binders and strontium hexaferrite powder, the material was cast in an injection molding machine to create the first intermediate (green) parts, followed by removal of the primary binder to obtain brown parts and final sintering.   Methods. Strontium hexaferrite powder was obtained by the ceramic method. The material underwent grinding in a planetary ball mill to obtain a powder having an average particle size of 13.4 μm, which is considered optimal for the applied PIM technology. Granulate materials, consisting of the obtained strontium hexaferrite powder combined with primary paraffin and secondary polyamide binders, were prepared by manual mixing of the components and used for creation of green parts in injection molding machine. Brown parts obtained following removal of binder from the obtained green parts were characterized by their higher brittleness and open pore structure. Permanent magnets with dimensions of 10 × 10 × 5 mm were obtained following sintering of brown parts in an oxidizing atmosphere.   Results. The more than 70% higher strength of the magnetic properties of the obtained strontium hexaferrite samples compared to isotropic barium hexaferrite-based magnets manufactured in accordance with GOST 24063-80 is due to the presence of pores after sintering.   Conclusions. The possibility of using the ceramic method for producing strontium hexaferrite powder for use in granulate manufacturing was demonstrated. This raw material can then be used to obtain strontium hexaferrite permanent magnets via PIM technology having 80 % density.